Inclusive recruitment? Hiring discrimination against older workers - Nick Drydakis; Peter MacDonald; Vasiliki Bozani; Vangelis Chiotis (Global Labor Organization (GLO), 2017)
Addressing population ageing requires a rise in the activity rates of older workers. In this study, a field experiment for the period 2013-2015 in the UK, suggests that age discrimination persists at alarming levels. It shows that when two applicants engage in an identical job search, the older applicant would gain fewer invitations for interviews regardless of her/his experience or superiority for the appointment. The results also suggest that older applicants face higher occupational access constraints for blue-collar jobs than white-collar/pink-collar jobs, and that women face greater age discrimination than men. Worryingly, the outcomes suggest that older applicants gain poorer access to vacancies than younger applicants irrespective of written commitments to equal opportunities. The design of the study suggests that discrimination results from distaste for older applicants, which has not been eliminated by the introduction of anti-discrimination legislation. Eliminating ageism in recruitment requires organizations to adopt more inclusive HR policies at the earliest stages of the recruitment process. Social dialogue has a crucial role to play in shaping inclusive and discrimination free recruitment policies such that shared values and beliefs are not age-discriminatory but rather recognize the strengths and potential of workers from different age groups.
Keywords: C93; C9; J14; J1; 330; Access to Occupations; Wages; Ageism; Women; Discrimination